2021
DOI: 10.1038/s41598-021-85412-1
|View full text |Cite
|
Sign up to set email alerts
|

Small compounds mimicking the adhesion molecule L1 improve recovery in a zebrafish demyelination model

Abstract: Demyelination leads to a loss of neurons, which results in, among other consequences, a severe reduction in locomotor function, and underlies several diseases in humans including multiple sclerosis and polyneuropathies. Considerable clinical progress has been made in counteracting demyelination. However, there remains a need for novel methods that reduce demyelination while concomitantly achieving remyelination, thus complementing the currently available tools to ameliorate demyelinating diseases. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Indeed, when applied in spinal cord injury models as a recombinant glycoprotein or when overexpressed by adeno-associated virus in stem cell-derived neural Biomolecules 2022, 12, 439 2 of 16 aggregates, Schwann cells and radial glial cells, L1 accelerated remyelination and improved axonal regrowth/sprouting/sparing proximal, distal and across the lesion site [9][10][11][12]. In addition, L1 ameliorated the severe consequences of injury in experimental models of neurodegenerative diseases in vitro and in vivo [13][14][15][16][17]. Since the viral delivery of L1, application of recombinant L1, and injection of stem cells overexpressing L1 are expected to meet difficulties in translation to therapy, libraries of small organic molecules were screened for compounds that structurally and functionally mimic L1, and several molecules were found to act as L1 agonistic mimetics [18].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when applied in spinal cord injury models as a recombinant glycoprotein or when overexpressed by adeno-associated virus in stem cell-derived neural Biomolecules 2022, 12, 439 2 of 16 aggregates, Schwann cells and radial glial cells, L1 accelerated remyelination and improved axonal regrowth/sprouting/sparing proximal, distal and across the lesion site [9][10][11][12]. In addition, L1 ameliorated the severe consequences of injury in experimental models of neurodegenerative diseases in vitro and in vivo [13][14][15][16][17]. Since the viral delivery of L1, application of recombinant L1, and injection of stem cells overexpressing L1 are expected to meet difficulties in translation to therapy, libraries of small organic molecules were screened for compounds that structurally and functionally mimic L1, and several molecules were found to act as L1 agonistic mimetics [18].…”
Section: Introductionmentioning
confidence: 99%
“…L1 cell adhesion molecule (L1CAM, hereafter abbreviated L1) has been shown to reduce the severe consequences of neurological diseases, such as multiple sclerosis [1], Parkinson's [2], and Alzheimer's [3] disease, in mouse and zebrafish models. The study of these models has led to the view that the disease-adverse phenotypes could be reduced by treatment with neural stem cells overexpressing L1, administration of recombinant extracellular domain of L1, function triggering L1 antibodies, and L1-derived peptide interacting with itself, i.e., homophilically with L1 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, zebrafish is an outstanding model system to perform number of neurodegenerative disorders (HD, AD, PD, PD, and MS), due to several advantages over the other experimental animals which includes, easy to genetic manipulation, low cost, fast development and large progeny (16,17).The physiology of zebrafish is similar to human being (more than 75%). Evidenced suggested that zebrafish as an excellent animal model for the study of several brain disorders such as Alzheimer's disease (AD) (18,19), Parkinson's disease (20), stress (21), epilepsy (22,23), dementia (24), cognition (25,26), Multiple sclerosis (MS) (27), Amyotropic lateral sclerosis (ALS) (28,29), and TBI (30).…”
mentioning
confidence: 99%